Readiness of Health Centers in Southwest Sumba Regency in Implementing Electronic Medical Records - Dadut, Ronaldus Asto; Ayu, Ayu Trinugrahani Steven (Tadulako University, 2025)
In Indonesia, every health service facility, including community health centers, is required to implement electronic medical records with a deadline of December 31, 2023. However, there are still 49 percent of national community health centers that still use manual medical records. One of the districts that plans to immediately implement electronic medical records is Southwest Sumba. This study conducted an analysis DOQ-IT method. There are 12 items that are combined into 2 categories, namely alignment and capacity of community health centers. This study is a quantitative descriptive study. The population was all health workers in 16 community health centers in Southwest Sumba. Data collection used questionnaires by random sampling. There were 79 questionnaires that were returned and were worthy of further analysis using descriptive analysis. The total readiness score of 16 health centers in Southwest Sumba in implementing electronic medical records is 76, which is included in quite ready. There are 9 items out of 12 readiness items that are included in the category of quite ready. The items in question are cultural readiness, leadership, strategy, clinical and administrative staff, training, workflow processes, finance and budget, patient involvement, IT support and management. However, there are still 3 items are not ready, namely information management, accountability, and IT infrastructure. Study found that all health centers showed a quite ready category through the DOQ-IT analysis. These results explain that the readiness of management information, IT infrastructure, and accountability need to be improved.